SISTEM KOMPUTERISASI ADMINISTRASI SURAT DI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS SAHID SURKARTA - Veronica Sri Yunitasari; Dahlan Susilo; Firdhaus Hari Saputro Al Haris (JURNAL GAUNG INFORMATIKA, 2015)
Correspondence Information System is a system built with the needs of matters relating to the activities of the letter - correspondence. Correspondence information system is built using the PHP programming language and MySQL database. Every user has different permissions. The existence of this system the user can easily create letters quickly as the letter associated with the final project and job training and letters associated with other Information Engineering study program and equipped with facilities to upload your inbox so that the performance of the user to be more effective and efficient .Testing this letter information system using black box method is the method of testing software that tests the functionality of the application as opposed to the internalstructure or work. System test results showed no significant obstacles found in normal use, most users are satisfied with this system with the services provided.